The Determinants of the Low COVID-19 Transmission and Mortality Rates in Africa: A Cross-Country Analysis - Bouba, Yagai; Tsinda, Emmanuel Kagning; Fonkou, Maxime Descartes Mbogning; Mmbando, Gideon Sadikiel; Bragazzi, Nicola Luigi; Kong, Jude Dzevela (Frontiers in Public Health, 2021)
Background: More than one year after the beginning of the international spread of COVID-19, the reasons explaining its apparently lower reported burden in Africa is still to be fully elucidated. Few studies previously investigated the potential reasons explaining this epidemiological observation using data at the level of a few African countries. However, an updated analysis considering the various epidemiological waves and variables across an array of categories, with a focus on African countries might help to better understand the COVID-19 pandemic on the continent. Thus, we investigated the potential reasons for the persistently lower transmission and mortality rates of COVID-19 in Africa. Methods: Data were collected from publicly available and well-known online sources. Cumulative numbers of COVID-19 cases and deaths per one million population reported by African countries up to February 2021 were used to estimate the transmission and mortality rates of COVID-19, respectively. Covariates were collected across several data sources: clinical/diseases data, health system performance, demographic parameters, economic indicators, climatic, pollution and radiation variables, and use of social media. Collinearities were corrected using variance inflation factor (VIF) and selected variables were fitted to a multiple regression model using the R statistical package. Results: Our model (adjusted R-squared: 0.7) found that the number of COVID-19 tests per one million population, GINI index, global health security (GHS) index and mean body mass index (BMI) were significantly associated (P<0.05) with COVID-19 cases per one million population. No association was found with the median life expectancy, proportion of rural population and BCG coverage rate. On the other hand, diabetes prevalence, number of nurses and GHS index were found to be significantly associated with COVID-19 deaths per one million population (adjusted R-squared of 0.5). Moreover, the median life expectancy and lower respiratory infections rate showed a trend towards significance. No association was found with BCG coverage or communicable disease burden. Conclusions: Low health system capacity, together with some clinical and socio-economic factors were predictors of the reported burden of COVID-19 in Africa. Our results emphasize the need for Africa to strengthen its overall health system capacity to detect and respond to public health crises.